LEARNERS’ INTEREST IN NEW NORMAL - Setiawati Setiawati; Dini Deswarni; Widia Yunita (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aims to know learners’ interest with blended learning at new normal period at the second, fourth, and sixth semesters of English Department, Islamic Religion Department, Islamic Banking Department, Islamic community Development Department of  STAI Hubbulwathan Duri. This research used quantitative approach. The design of the research was a survey research. Total population was 260 respondents. The undergraduate students have the same qualification and academic background before doing survey. They had ever learned by using blended learning in a new normal situation. Sample of this research was 155 respondents. The total rating percentage of learners’ interest in involving in the blended learning was 69.98 %. it was in “agree category”. This category showed the respondents’ interest  in blended learning process. Based on overall mean is 2.82 and standard deviation is 0.54. The respondents agree used to have the blended learning activities in their learning process. It means that the learners’ had good interest in their blended learning activities.